The Influence Of Digital Financial Literacy And Consumptive Lifestyle On The Decision To Use Shopee Paylater Among Gen Z Students (Case Study On Management Students At Dehasen University, Bengkulu) - Rhamadan, Danny; Susanti , Neri; Dennis , Dennis (Journal of Law, Social Science, and Management Review, 2025)
This study aims to determine the influence of digital financial literacy and consumptive lifestyle on the decision to use Shopee PayLater among Generation Z students at Dehasen University, Bengkulu. The study employed an associative quantitative approach with a purposive sampling method involving 86 respondents. Data were collected through an online questionnaire and analyzed using multiple linear regression analysis with the help of SPSS version 25.The results showed that digital financial literacy has a significant effect on the decision to use Shopee PayLater, with a t-value of 3.928 > t-table of 1.663 and a significance level of 0.00 < 0.05. Consumptive lifestyle also has a significant effect on the decision to use Shopee PayLater, with a t-value of 7.345 > t-table of 1.663 and a significance level of 0.00 < 0.05. Simultaneously, both variables have a significant effect, with an F-value of 69.443 > F-table of 3.11 and a significance level of 0.000 < 0.05. The R² value of 0.626 indicates that these two variables explain 62.6% of the variation in the decision to use Shopee PayLater. The multiple linear regression equation is expressed as Y = 0.403 + 0.408(X1) + 0.575(X2) + e. Thus, the higher the level of digital financial literacy and the more consumptive the students’ lifestyle, the greater the likelihood that they will use Shopee PayLater.